A survey of organic farming in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in Plant Science at Massey University - Bakker, Rosalie Jeanne (Massey University, 1993)
The characteristics of organic farms and farmers were studied and management factors determined. The effects of changing over to an organic farming system were also examined. A postal survey was sent to 77 organic farms and 32 conventional farms around New Zealand. Farmers use organic methods for pragmatic rather than spiritual reasons. The majority come from diverse occupational backgrounds before becoming a farmer, unlike most conventional farmers who had been farmers all their working life. Organic farms averaged 123 hectares, of which 83% was used for actual organic production. The conventional farms averaged 410 hectares. Properties usually had two or more types of farm enterprises present with organic farms being more diverse: beef, vegetables and fruit being the more popular choices. Conventional farmers tended to stay with the more traditional enterprises of sheep, beef and wool. Grazing and cropping systems on organic farms were not significantly more soil conservative. Compost and fish fertilisers were the most frequently used fertilisers on organic farms with reactive phosphate rock as a phosphate source. Conventional farmers used the traditional superphosphate, potassium super, longlife super and urea. Lime was used by both groups. Organic farmers ranked internal parasites worse than any other problem, whilst conventional farmers felt it to be about equal to flystrike. Facial eczema and grass staggers noted as problems by the conventional group, were not even mentioned by the organic farmers. Thistles were a much bigger weed problem on organic farms than on conventional properties. Changing to organic farming did not change these problems, nor was there any significant difference in intensity of control methods used between the two farming systems Over a quarter of the organic farmers were involved in some processing of produce on their property, and on average labelled this as organic. Forty percent of organic produce was sold to conventional outlets. Fifty-four percent of organic farmers and 94% of conventional farmers had all or nearly all of their income provided by their property. There was no significant difference between organic or conventional properties concerning labour. Organic farming did not significantly change yields and income per hectare, either in the first or subsequent years after changing from conventional farming. Labour requirements also remained the same. In conclusion, the majority of all the farmers surveyed felt satisfied with their present farming system.
Keywords: 300801 Field organic and low chemical input horticulture